IMPLEMENTATION OF JOINT VENTURE BASED OF MULTINATIONAL CORPORATION IN THE EXPANDING BUSINESS MARKET FOR EUROPE AREA MARKETING PROGRAM - Odhyza Prakarsa Razak; Endy Gunanto Marsasi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2023)
Bukit Asam Tbk is a coal mining company owned by the Indonesian state. This research was conducted to try to help create new marketing programs by applying for programs. The method for analyzing this research is qualitative by direct observation, in-depth interviews, collection of documentation, and secondary data of the company. The research was conducted in the company through the marketing division. This research resulted in a marketing program using the MNC concept with the implementation of joint ventures which are expected to be implemented in the PT. Bukit Asam Tbk.